2019
DOI: 10.1111/jcpt.12817
|View full text |Cite
|
Sign up to set email alerts
|

Impact of voriconazole plasma concentrations on treatment response in critically ill patients

Abstract: Summary What is known and objective Several authors have demonstrated the relationship between voriconazole concentrations and the risk of therapeutic failure and adverse events However, the information about voriconazole concentrations in the critically ill patient is scarce. The aim of this study was to analyse the plasma concentrations and pharmacokinetic behaviour of voriconazole in critically ill patients and their association with the treatment response and development of toxicity. Methods A prospective,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
31
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 36 publications
4
31
1
Order By: Relevance
“…In our study, presenting the largest patient cohort simultaneously treated with voriconazole and ECMO, the extensive intra- and interpatient variability in voriconazole exposure was confirmed [ 1 , 16 , 24 , 27 ]. Therapeutic drug monitoring (TDM) is recommended and performed in clinical practice but despite drug monitoring, we still found 48% subtherapeutic samples, which is a lot, certainly in this severely ill population.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…In our study, presenting the largest patient cohort simultaneously treated with voriconazole and ECMO, the extensive intra- and interpatient variability in voriconazole exposure was confirmed [ 1 , 16 , 24 , 27 ]. Therapeutic drug monitoring (TDM) is recommended and performed in clinical practice but despite drug monitoring, we still found 48% subtherapeutic samples, which is a lot, certainly in this severely ill population.…”
Section: Discussionmentioning
confidence: 61%
“…This is a high proportion but corresponds to the proportions described in two previous published studies in critically ill patients (48% and 53%) [ 24 , 25 ]. In contrast, several other studies reported lower rates of subtherapeutic voriconazole concentrations, around 20%, although in some studies in a population only partially admitted at the ICU [ 26 , 27 , 28 , 29 ]. In all the above-mentioned studies, voriconazole trough concentrations were considered subtherapeutic if lower than 1.0 or 1.5 mg/L, while we defined a lower limit of > 2 mg/L.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…29 Ruiz et al conducted a prospective study with 33 critically ill patients, and the VPC outside the optimum range (1.0-5.5 mg/L) was observed in 15 patients (45.5%), and VPC greater than 5.5 mg/L was closely related to the development of hepatotoxicity. 30 Myrianthefs et al conducted a small sample prospective study with 18 ICU patients and found that the VPC of 53% (16/30) of the critically ill patients was less than 1 mg/L, and after administering a loading dose of 6 mg/kg followed by a maintenance dose of 3-4 mg/kg, no adverse events occurred in the study. 31 These results indicated that there was a high variation in VPC in critically ill patients, and the correlations between VPC and adverse events were not obvious.…”
Section: Discussionmentioning
confidence: 99%
“…Yi et al performed a retrospective study with 122 patients (47% of the patients were critically ill) to investigate the distribution of VPC, and the results showed that 61% of the patients reached the optimum range (1‐5.5 mg/L), and non‐therapeutic VPC was strongly related to adverse events requiring discontinuation 29 . Ruiz et al conducted a prospective study with 33 critically ill patients, and the VPC outside the optimum range (1.0‐5.5 mg/L) was observed in 15 patients (45.5%), and VPC greater than 5.5 mg/L was closely related to the development of hepatotoxicity 30 . Myrianthefs et al conducted a small sample prospective study with 18 ICU patients and found that the VPC of 53% (16/30) of the critically ill patients was less than 1 mg/L, and after administering a loading dose of 6 mg/kg followed by a maintenance dose of 3‐4 mg/kg, no adverse events occurred in the study 31 .…”
Section: Discussionmentioning
confidence: 99%